PENGARUH KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI FLOW DISTRO PREMBUN (Prospect : Jurnal Manajemen dan Akuntansi, 2021)
Service quality is the main milestone in the company's running activities. In general, providing good and maximum service will encourage consumers to make purchasing decisions. This has a very good impact on the company's goal, namely to increase sales output. The aim of this research is to determine "The Influence of Service Quality on Purchasing Decisions at Flow Distro Prembun". Samples were taken using the Simple Random Sampling technique. The average number of Kios Insan Busana consumers per month can reach 400 people. As research subjects, 25% of all consumers at the Insan Busana Kiosk were taken, namely 100 consumers. From the t test, it can be concluded that the Service Quality variable has a positive and significant effect on the purchasing decision variable because it has a significance of 0.000 (P> 0.05) and the tcount > ttable (8,781 > 1.984). So hypothesis 0 which states that there is no positive and significant influence between service quality and purchasing decisions is rejected and the working hypothesis (Ha) which states that there is a positive and significant influence between service quality and purchasing decisions is accepted.